2009
DOI: 10.5688/aj730227
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Students' Ability to Identify Potential Drug-Drug Interactions

Abstract: Objective. To evaluate the ability of third-and fourth-year pharmacy students to identify clinically significant drug-drug interactions (DDIs) Methods. A questionnaire designed to measure DDI knowledge was disseminated to fourth-year pharmacy students in a school of pharmacy. A second questionnaire was distributed to third-year pharmacy students in 2 schools of pharmacy (schools A and B) and re-administered to students in 1 of the schools 1 year later. Results. Class of 2005 fourth-year pharmacy students corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 19 publications
1
18
0
2
Order By: Relevance
“…17,25,26 Saverno and colleagues found that DDI educational sessions improved pharmacy students' short-term knowledge. 25 Trujillo and colleagues offered a 2-semester drug interaction elective course to third-year pharmacy students; students completing the course showed improved DDI recognition scores and increased confidence in identifying interactions in comparison to their peers who opted out of the course. 17 Tskuruoka and colleagues evaluated 2 physician groups from the same undergraduate medical school who had been in clinical practice for 3 to 7 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,25,26 Saverno and colleagues found that DDI educational sessions improved pharmacy students' short-term knowledge. 25 Trujillo and colleagues offered a 2-semester drug interaction elective course to third-year pharmacy students; students completing the course showed improved DDI recognition scores and increased confidence in identifying interactions in comparison to their peers who opted out of the course. 17 Tskuruoka and colleagues evaluated 2 physician groups from the same undergraduate medical school who had been in clinical practice for 3 to 7 years.…”
Section: Discussionmentioning
confidence: 99%
“…However, DDI information aids do not replace the need for healthcare providers to have a basic understanding of important drug interactions. 25 This study tested and retested the same pharmacy, medical, and nursing students with the same test instrument pre-and posttraining, potentially introducing testing bias. The threat is especially relevant given that the posttest was administered immediately following the educational session.…”
Section: Discussionmentioning
confidence: 99%
“…The students and the residents can be considered a result of the combination of their knowledge and skill to use documentary tools. Our foreign colleagues have already realized a myriad of works pertaining to this matter (to see, for example, reference [76] regarding the medicinal interactions). Girollet et al, by conducting a national study to know the realized ACT-IPß project: Ten years onward, results and prospects activities and the feelings of the students regarding the internships scheduled during the studies of pharmacy, recently highlighted the good reasons and the urgency to take action: the fact that 53% of the students in hospital training declared not having been acquainted with the prescription of drugs; 74% did not participate in the dispensation of drugs [77].…”
Section: Develop Educational Strategies For the Students And Residentsmentioning
confidence: 99%
“…En effet, la diversité des IP réalisées par les étudiants et les internes peut être regardée comme résultant de la combinaison de leurs savoirs et de leur compétence à employer les outils documentaires. Nos confrères étrangers ont déjà réalisé une myriade de travaux à ce sujet (voir par exemple la référence [76] concernant les interactions médicamen-teuses). Girollet et al, en réalisant une étude nationale visant à connaître les activités réalisées et le ressenti des étudiants concernant les stages programmés au cours des études de pharmacie, ont récemment mis en évidence les bonnes raisons et l'urgence de passer à l'action : le fait que 53 % des étudiants en stage hospitalier ont déclaré ne pas s'être familiarisé avec la prescription des médicaments ; 74 % n'ont pas participé à la dispensation des médicaments [77].…”
Section: Développer Et Appliquer Aux Stages Professionnalisants Des Sunclassified